Molecular saturation determines distinct plasmonic enhancement scenarios for two-photon absorption signal - Saeid Izadshenas Jahromi; Karolina Słowik (Scientific Reports)
Abstract Two-photon absorption in molecules, of significance for high-resolution imaging applications, is typically characterised with low cross sections. To enhance the TPA signal, one effective approach exploits plasmonic enhancement. For this method to be efficient, it must meet several criteria, including broadband operational capability and a high fluorescence rate to ensure effective signal detection. In this context, we introduce a plus-shaped silver nanostructure designed to exploit the coupling of bright and dark plasmonic modes. This configuration considerably improves both the absorption and fluorescence of molecules across near-infrared and visible spectra. By fine-tuning the geometrical parameters of the nanostructure, we align the plasmonic resonances with the optical properties of specific TPA-active dyes, i.e., ATTO 700, Rhodamine 6G, and ATTO 610. The expected TPA signal enhancement is evaluated using classical estimations based on the assumption of independent enhancement of absorption and fluorescence. These results are then compared with outcomes obtained in a quantum-mechanical approach to evaluate the stationary photon emission rate. Our findings reveal the important role of molecular saturation determining the regimes where either absorption or fluorescence enhancement leads to an improved TPA signal intensity, considerably below the classical predictions. The proposed nanostructure design not only addresses these findings, but also might serve for their experimental verification, allowing for active polarization tuning of the plasmonic response targeting the absorption, fluorescence, or both. The insight into quantum-mechanical mechanisms of plasmonic signal enhancement provided in our work is a step forward in the more effective control of light-matter interactions at the nanoscale.